Toward a certification protocol for Positive Energy Districts (PED). A methodological proposal - Volpatti, Marco; Mazzola, Elena; Bottero, Marta Carla; Bisello, Adriano (TeMA - Journal of Land Use, Mobility and Environment, 2024)
In order to achieve the ambitious CO2 emission reduction targets, set by the Sustainable Development Goals, it is crucial to act on cities. Indeed, cities are responsible for 67% of the world’s primary energy consumption and about 70% of energy-related CO2 emissions. To support the urban energy transition, a broad implementation of zero-emission districts or, even better, positive energy districts (PEDs) is expected. PEDs can be defined as energy-efficient and energy-flexible urban areas that aim to provide a surplus of clean energy to the city by using renewable energies. However, in developing the PEDs concept, it is necessary to consider not only the technical issue of energy systems but also the environmental, social, and economic spheres. To be effective, it is important to provide decision-makers with tools such as protocol certification for PEDs, which can effectively assess the complexity of the impacts a PEDs might have on other urban transformations from a multi-stakeholder perspective. LEED for neighborhood development, BREEAM communities, and CASBEE for cities are the most widely used and known protocols in the world for the evaluation of districts. Protocol certifications today do not consider PEDs because they are outdated, but some common characteristics can already be found within them, which allows for the possibility of reformulating scores and inserting new evaluation criteria. The aim of this research, through a review of the literature, is to analyze the current protocol certificates at the district level, identifying criteria and scores within the evaluation methods, with the aim of contributing to the definition of a PED certification protocol with effective criteria and scores to support design and development of PEDs.